Systematic Bibliometric Analysis of Research Hotspots and Trends on the Application of Virtual Reality in Nursing - Zhao, Junqiang; Lu, Yi; Zhou, Fujun; Mao, Ruping; Fei, Fangqin (Frontiers in Public Health, 2022)
Background: With the emergence of the metaverse, virtual reality, as a digital technology, must be getting hotter. High quality virtual reality related nursing knowledge scene learning is gradually replacing traditional education and intervention skills. Objective: This systematic study aimed to gain insights into the overall application of virtual reality technology in the study of nursing. Methods: Citations downloaded from the Web of Science Core Collection database for use in VR in nursing publications published from January 1, 2012, to December 31, 2021, were considered in the research. Information retrieval was analyzed using https://bibliometric.com/app, CiteSpace.5.8. R3, and VOS viewer. Results: A total of 408 institutions from 95 areas contributed to relevant publications, of which the United States is the most influential country in this research field. The clustering labels of cited documents were obtained from the citing documents. Virtual simulation, virtual learning, clinical skills, and dementia are the clustering labels of co-cited documents. The burst keywords represented the research frontiers in 2020–2021, which were knowledge and simulation. Conclusions: Virtual nursing has had an impact on both nurses and clients. With the emergence of the concept of the metaverse, the research and application of virtual reality technology in nursing will gradually increase.